Prediction of the risk of mortality in paediatric intensive care unit using PRISM III score - Shah, Aashay Abhay; Goyal, Dileep; Sareen, Devendra (International Journal of Contemporary Pediatrics, 2019)
Background: is the Pediatric risk of mortality (PRISM) score which has been devised by Pollock et al, to predict the mortality in hospitalized children. PRISM score is a revised form of physiologic stability index of mortality score. Methods: A observational prospective study was conducted at tertiary care hospital, Udaipur Rajasthan over period of March 2017 to September 2018. Total 207 patient were enrolled in study as per inclusion and exclusion criteria. Results: Total 29.92% had PRISM III score of 0 to 5, 25.45% had score of 6-10, 16.53% had score of 11-15, 13.12% had score of 16-20, 7.61% between 21 to 25, 4.72% between 26-30 and 2.62% had score of greater than 30. There was no mortality when the PRISM score of the child was between 0 to 5. The percentage of deaths increased progressively with increasing PRISM score. Conclusions: There was no significance difference in predicted from PRISM score and the actual death. The expected mortality was comparable to actual death, except in children who required mechanical ventilation and vasopressor drugs.